Toxic Effects Of Signal Grass (Brachiaria Decumbens) On Drug- Metabolizing Enzyme Activities In Sheep - Hussain, Mohd Khairi (2003)
Signal grass (Brachiaria decumbens) is widely grown on livestock farms in many countries including Malaysia due to its high productivity and nutritive value. Unfortunately, it is toxic to sheep and goats causing a severe hepatic and renal damage, and death. Two experiments were conducted to determine the effect of the toxicity of signal grass (B. decumbens) on the activity of drug-metabolizing enzymes (DME) in sheep and cattle. It was hypothesized that the activities of selected enzymes would be affected during intoxication and that differences in the activity level of the enzymes in the two species might explain why cattle were safe from the toxic effect of the grass. Twenty-three healthy Wiltshire-Malin crossed rams, aged 1 4- 1 6 months were used, fifteen for the first experiment and eight for the later. In the first experiment, aniline 4-hydroxylase (A4H), aminopyrine N-demethylase (AND), UDP-glucuronyl transferase (UDPGT), glutathione S-transferase (GST) and cytochrome P450 of the liver and kidney of the control and intoxicated sheep were